2005
DOI: 10.1055/s-2005-871297
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Flavonoids fromFlemingia macrophylla

Abstract: Using an Abeta-induced neurotoxicity blocking assay to direct fractionation, three new flavonoids, fleminginin (1), flemingichromone (2), and flemingichalcone (3), and twenty known compounds were isolated from the active fractions of the aerial parts of Flemingia macrophylla. The structures of 1 - 3 were elucidated on the basis of spectroscopic data. When tested for neuroprotective activity, compound 2, osajin ( 4), 5,7,4'-trihydroxy-6,8-diprenylisoflavone (5), 5,7,4'-trihydroxy-6,3'-diprenylisoflavone (6), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 14 publications
0
30
0
1
Order By: Relevance
“…The chemical investigation of the roots of F. philippinensis led to the isolation of three new (1-3) and twelve known compounds (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The structures of 1-3 were elucidated on the basis of their spectroscopic data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical investigation of the roots of F. philippinensis led to the isolation of three new (1-3) and twelve known compounds (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The structures of 1-3 were elucidated on the basis of their spectroscopic data.…”
Section: Discussionmentioning
confidence: 99%
“…Several species are used as ethnodrugs for a long history to cure rheumatoid arthritis, lumbocrural pain, lumbar muscle strain, swollen feet, chronic nephritis, menopausal syndrome and so on [1]. Previous chemical investigations have demonstrated that the genus is a rich source of isoflavonoids, chalcones, flavones, terpenoids, and phenolics [2][3][4][5][6], exhibiting various biological activities [5][6][7][8]. Among them, isoflavonoids are the major bioactive ingredients and have been obtained from the roots, stems, flowers and seeds of the Flemingia plants, some of which exhibit anti-cancer, antioxidant and chemical protective activities [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The root and stems of Flemingia macrophylla , a polyphenol-rich member of the Fabaceae family of flowering plants, are used as a folk medicine in many Asian countries to treat rheumatic, inflammatory, and blood circulation disorders [11]. It has been reported that Flemingia macrophylla extract (FME) shows analgesic and anti-inflammatory activities in mice [12] as well as antioxidant and hepatoprotective effects in rats [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Flemingia macrophylla extract (FME) shows analgesic and anti-inflammatory activities in mice [12] as well as antioxidant and hepatoprotective effects in rats [13]. Furthermore, the flavonoids in Flemingia macrophylla have been demonstrated to inhibit A β -induced neurotoxicity [11]. Flemingia macrophylla is rich in polyphenols such as daidzin, daidzein, genistin, genistein, flemingin A, and flemingin D [11, 14].…”
Section: Introductionmentioning
confidence: 99%
“…As a traditional Chinese medicine (TCM) listed in the Chinese Pharmacopoeia, it has been widely used to cure rheumatism, lumbar muscle strains, myasthenia of limbs, injuries from falls, swelling, sore throats, etc . [1,2,3]. Although Radix Flemingiae Macrophyllae contains tens or even hundreds of compounds, only a limited number of compounds, such as flavonoids and the volatile constituents, might be responsible for the pharmaceutical or toxic effects [4,5,6].…”
Section: Introductionmentioning
confidence: 99%